Effects of Hydroponic Maize Fodder with and Without Supplementation of Probiotics (Saccharomysis cerevisiae) on Rumen Parameters in Calves - Joshi, Monika; Sharma, S. K.; Vaishnava, C. S. (International Journal of Bio-resource and Stress Management, 2024)
An experiment was conducted during October to January, 2018 at Gir Cattle Farm, College of Veterinary and Animal Science, Navania, Udaipur, Rajasthan, India to evaluate the effect of hydroponic maize fodder with and without supplementation of probiotics on rumen fermentation. A feeding trial of 120 days was conducted on 36 male Gir calves of same age group (6–12 months) and randomly allotted to nine dietary treatments. All the animals were offered basal feed ad lib. The T1 i.e. control group were fed concentrate mixture as per requirement. For calves in T2, T3, T4 and T5 groups, 25%, 50%, 75% and 100% of crude protein (CP) supplied through concentrate mixture was replaced by hydroponics maize green fodder, respectively. Whereas, in T6, T7, T8, T9 groups, 25% 50%, 75% and 100% of crude protein (CP) supplied through concentrate mixture was replaced by hydroponics maize green fodder along with probiotics, respectively. All the rumen parameters viz. pH, Total protozoal count (105 ml-1), Total Volatile Fatty Acids (meq l-1), Ammonia nitrogen (mg dl-1), Total nitrogen (mg dl-1), TCA-precipitable nitrogen (mg dl-1), and Non protein nitrogen (mg dl-1), were estimated according to treatment and time intervals. There was non-significant effect of treatments on rumen pH but due to time intervals were found to be highly significant (p<0.01). The concentration of Total protozoal count, Total volatile fatty acids (TVFA), Total ammonia nitrogen (NH3–N), Total nitrogen, TCA- Precipitable N and Non-Protein Nitrogen (NPN) were highly significant (p<0.01) effect due to treatments and time intervals.